IMPLEMENTASI STRATEGI PEMBELAJARAN BAGI ANAK BERKEBUTUHAN KHUSUS DI RUMAH BELAJAR KEVALA - Tiara Dwi Cahyaning Wulandari; Alfi Zahra Fahira; Luthfiah Aulia Nurul Akmal; Tadya Nastari Septia Anwar (Jurnal Citra Pendidikan, 2025)
Inclusive education aims to provide equal learning access for every individual, including children with special needs (CSN). This study aims to analyze and identify the learning strategies implemented at Rumah Belajar Kevala in creating effective education for children with special needs. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results show that Rumah Belajar Kevala implements various learning strategies, such as project-based, collaborative, and adaptive methods, designed to meet the individual needs of students. The main focus of learning is on the development of independence (Activity of Daily Living), behavior, and social skills. This approach also involves active parental involvement to support the continuity of learning at home. The implementation of these strategies has proven effective in enhancing students’ independence, active participation, and social abilities. The conclusion of this study is that Rumah Belajar Kevala has successfully created relevant, flexible, and adaptive learning strategies for CSN, making it a model for the development of similar educational practices.